ESP COURSE DESIGN: THE NEED ANALYSIS ON TOURISM DEPARTMENT IN INDONESIA VOCATIONAL HIGH SCHOOLS - Asrifan, Andi; Vargheese, K. J.; T., Syamsu; Amir, Muhammad (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
Centered on the 2013 Curriculum (Indonesia's national curriculum), English subject matter is equated to the high school standard. Both high school and vocational school students receive the same English content, while English is to be differentiated for special purposes for high school and vocational high school students. It is difficult to find an English textbook in a vocational school which fits into the department of the student. Additionally, there is often not enough time for teachers to develop English materials for vocational students. This study aims to explore the content that should be included in SMKN 1 Pangsid Kabupaten Sidenreng Rappang to design English language materials based on needs analysis in the Tourism Program and to find out the response of teachers to the development of English material in the Tourism Programme. Fundamental analysis uses Qualitative Descriptive, and the findings are described in terms. The study results indicate that the content to be included in the English language material in the SMKN 1 Pangsid Kabupaten Sidenreng Rappang tourism program is speaking and pronunciation for language skills and components; media videos and images; and asking questions about teaching techniques. Creation of English language materials consists of several speaking practice presentations, many videos to practice listening, speaking and reading, reading sections and documents, and some information that the Tourism Program learners need to know.